2016
DOI: 10.1016/j.jdent.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Repair of defective composite restorations. A questionnaire study among dentists in the Public Dental Service in Norway

Abstract: The idea of "minimal intervention dentistry" seems to have great influence among dentists in PDS (Norway), as they seek to preserve dental hard tissue as much as possible by choosing repair before replacement. No gender differences were observed, but older dentists seem to favour repair compared with the younger dentists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 92 publications
(95 reference statements)
1
18
0
16
Order By: Relevance
“…The use of burs, followed by acid etching and application of a bonding agent, appeared to be used by over 80% of clinicians as a pretreatment for the old composite for repair [5]. This was also the most commonly taught procedure for dental students in their curriculum [2,3,23,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of burs, followed by acid etching and application of a bonding agent, appeared to be used by over 80% of clinicians as a pretreatment for the old composite for repair [5]. This was also the most commonly taught procedure for dental students in their curriculum [2,3,23,28].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey among Norwegian dentists, it was found that almost eight out of nine dentists preferred repair of failed restorations when damage was small [5]. …”
Section: Introductionmentioning
confidence: 99%
“…O reparo de parte do material restaurador defeituoso, tornou-se uma forma de atrasar ou interromper a cascata do ciclo restaurador repetitivo, limitando a quantidade de substância dentária sacrificada e mantendo a sobrevivência dental por um espaço maior de tempo (Ferracane et al, 2011;Blum et al, 2012;Gordan et al, 2012;Opdam et al, 2012;Lynch et al, 2013;Blum et al, 2014;Fernandez et al, 2015;Casagrande et al, 2017;Estay et al, 2017;Kanzow et al, 2017b (Staxrud et al, 2016).…”
Section: 45unclassified
“…Nessas situações, um procedimento mais simples, como o reparo da restauração pode ser o tratamento mais apropriado, considerado minimamente invasivo, tão efetivo quanto a troca total da restauração, causando menor remoção de tecido sadio, aumentando a longevidade da restauração e reduzindo o risco de complicações do tratamento, a necessidade de anestesia local, o tempo operatório e o custo de todo o tratamento (Gordan et al, 2012;Lynch et al, 2013;Staxrud et al, 2016;Casagrande et al, 2017;Fornazari et al, 2017). Gordan et al (2014) A Odontologia Restauradora presume que a restauração dental é elaborada para devolver permanentemente a estrutura dental perdida, no entanto vários estudos têm apontado que a substituição tem sido vastamente executada.…”
Section: 45unclassified
See 1 more Smart Citation